Analytical View on The Use of Innovative Methods of Human Resource Management in Organizations with Implemented Talent Management - Jana COCULOVA; Daniela BERTOVA (Communications of International Proceedings, 2021)
The paper deals with the topic of talent management and innovative methods of human resource management, which should be used in organizations with implemented talent management. The paper presents the results of research conducted on a sample of Slovak organizations, which is focused on the analysis of the state of use of talent management in Slovak organizations. The partial goal of the research was to find out whether there are statistically significant differences in the rate of use of innovative methods of human resource management between the organizations that have implemented and those that did not implement talent management. Data collection took place through an electronic questionnaire in the period from March to June 2020. The subject of the research was innovative methods used in selected human resources management practices that are directly related to talent management, namely recruitment, evaluation of employee performance and training of employees. To meet the stated goal, 3 hypotheses were tested using Mann's Whitney U test. The results of the research showed that organizations with implemented talent management make more use of innovative methods in human resource management than organizations that have not implemented talent management.
Keywords: Human Resource Management; Human Resource Management Practices; Talent Management.